2018
DOI: 10.1002/jgt.22400
|View full text |Cite
|
Sign up to set email alerts
|

Spanning bipartite quadrangulations of even triangulations

Abstract: A triangulation (resp., a quadrangulation) on a surface double-struckF is a map of a loopless graph (possibly with multiple edges) on double-struckF with each face bounded by a closed walk of length 3 (resp., 4). It is easy to see that every triangulation on any surface has a spanning quadrangulation. Kündgen and Thomassen proved that every even triangulation G (ie, each vertex has even degree) on the torus has a spanning nonbipartite quadrangulation, and that if G has sufficiently large edge width, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Lukot'ka and Rollová [7] show that the feasible sets in cubic graphs could be used to show the existence of spanning bipartite qudrangulations (cf. [12]) and certain cycle covers in signed cubic bipartite graphs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lukot'ka and Rollová [7] show that the feasible sets in cubic graphs could be used to show the existence of spanning bipartite qudrangulations (cf. [12]) and certain cycle covers in signed cubic bipartite graphs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lukot'ka and Rollová [7] found that the Petersen graph has a nonfeasible edge set that is not switching-equivalent to either ∅ or E G ( ) and believed that an easy characterization of feasible edge sets for regular nonbipartite graphs does not seem possible. More such examples can be found in [12]. But all of these examples are non-3-edge-colorable cubic graphs, which are socalled snarks.…”
Section: Introductionmentioning
confidence: 99%
“…Is there a constant c(Σ) depending only on the surface Σ, such that if the edge-width of a triangulation G of Σ is at least c, then G has a weak 2-coloring? Kündgen and Thomassen [8], Nakamoto, Noguchi and Ozeki [15] independently addressed this question, and considered spanning quadrangulation subgraphs of a given triangulation G of Σ since the following proposition holds (e.g., [15,Proposition 7]). Proposition 2.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this concept first appeared in [9]. Lukot'ka and Rollová [9] proved that the feasible sets in cubic graphs could be used to show the existence of spanning bipartite quadrangulations (see [10]) and certain cycle covers in signed cubic bipartite graphs. Clearly, each edge in a matching covered graph G forms a trivial feasible set if V(G)3, while and E(G) are two trivial nonfeasible sets.…”
Section: Introductionmentioning
confidence: 99%
“…They also mentioned in [9] that an easy characterization of nonfeasible sets in regular nonbipartite graphs does not seem to be possible. More such examples can be found in [10]. Since all of these examples are snarks (which belong to the set of cubic graphs of class 2), Lukot'ka and Rollová [9] proposed the following problem.…”
Section: Introductionmentioning
confidence: 99%